1980
DOI: 10.1093/infdis/141.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Influenza B/Hong Kong Virus Infections among Infants, Children, and Young Adults

Abstract: An influenza B/Hong Kong viral epidemic was monitored by surveillance of respiratory illness in three different age groups. Prospective viral monitoring of febrile respiratory illness was a useful mirror of the epidemiologic behavior of influenza in the community. Influenza B virus infection in infants and young children was distinguished by high fever and respiratory symptoms and was occasionally associated with otitis media. In older children and young adults, systemic and gastrointestinal complaints were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 13 publications
4
25
0
1
Order By: Relevance
“…However, the HI antibody response to influenza B was poor (Table 2), as previously reported (Clark et al 1970;Wright, Bryant & Karzon, 1980). A fourfold or greater antibody response to B/Kanagawa HA antigen was seen in only 3-50% of the students tested, and the geometric mean HI titres remained unchanged at approximately 50-70.…”
Section: Serodiagnosis Of Natural Infection With Influenza a Virus Dusupporting
confidence: 71%
“…However, the HI antibody response to influenza B was poor (Table 2), as previously reported (Clark et al 1970;Wright, Bryant & Karzon, 1980). A fourfold or greater antibody response to B/Kanagawa HA antigen was seen in only 3-50% of the students tested, and the geometric mean HI titres remained unchanged at approximately 50-70.…”
Section: Serodiagnosis Of Natural Infection With Influenza a Virus Dusupporting
confidence: 71%
“…28 Again we saw that the HAI response to the influenza B vaccine component, and to natural influenza B infection, in young children is often limited. 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Studies of hospitalised influenza patients also report neurological symptoms, such as febrile convulsions [97, 115, 119], although these are often reported as complications of the disease rather than symptoms (see next section). As well as the neurological system, other non-respiratory systems can be commonly affected in influenza: in some epidemics, up to 50 % of children have presented with gastrointestinal symptoms such as vomiting and diarrhoea, particularly those who are admitted to hospital, and affecting children of all age groups [1, 11, 67, 69, 90, 134]. In a study of children and adolescents hospitalised with laboratory-confirmed influenza, sepsis-like illness was the admission diagnosis for 52 % of those aged <6 months and for up to 16 % of older children [115].…”
Section: Clinical Manifestations Of Diseasementioning
confidence: 99%